MITRAL REGURGITATION IN CHILDREN WITH MITRAL VALVE PROLAPSE. FEATURES OF ECHOCARDIOGRAPHIC INDICATORS - A. V. Kuleshov (Східноукраїнський медичний журнал, 2019)
Mitral valve prolapse plays an important role in cardiovascular pathology in children. The study reveals the condition of the central hemodynamic and echomorphometric parameters in children with mitral valve prolapse (MVP) taking into account mitral regurgitation.